Associations between morpho-agronomic characters in Conilon (Coffea canephora) 8142 (Research, Society and Development, 2020)
The work consisted of the morpho agronomic evaluation of coffee crop under the influence of intercropping with different types of green manures. The experiment was carried out in the Southern Region of the State of Espírito Santo, Brazil. The experimental plot consisted of five plants per experimental unit, using the clone "Incaper 8142" Conilon Vitória, intercropping with different types of green manure plants, which were: guandu beans (Cajanus cajan), pig bean (Canavalia ensiformis), mucuna preta (Mucuna Pruriens) and Mexican margaridão (Tithonia diversifolia) in addition to a control treatment without green manure. The planting consisted of rows adjacent and located in the “upper interline” meaning is not clear of the coffee crop. The morpho agronomic characteristics evaluated were: plant height, orthotropic branch diameter, plagiotropic branch diameter, number of leaves, number of nodes, number of orthotropic branches, number of plagiotropic branches and productive nodes e productivity green coffee kg/ha, besides the main dependent: The characteristics of greatest direct contribution were number of nodes and number of productive nodes. The species of green fertilizer Mexican Margaridão (Tithonia diversifolia) provided a negative effect on the main variables related to production, and is not recommended for interplanting with robusta coffee.